Results of Insulin Therapy in Type 2 Diabetes Mellitus Patients in the Czech Republic: Do They Reflect the Current Status in Other Countries? - Brož, Jan; Janíčková Ždárská, Denisa; Urbanová, Jana (Diabetes therapy, 2019)
The results of two large multicentric, observational and cross-sectional studies (the DIAINFORM study and BALI study) reflecting routine clinical practice for insulin treatment in type 2 diabetes mellitus in the Czech Republic were published recently. In this commentary, we analyze these results and compare them with the findings of similar studies conducted in other countries within the last decade. The analysis focuses on achievement of glycated hemoglobin goals, insulin dosage and frequency of hypoglycemia.
Keywords: HbA1c; Insulin titration; Type 2 diabetes; Hypoglycemia; Basal insulin initiation; Metabolic control